Combination of Erythromycin and Curcumin Alleviates Staphylococcus aureus Induced Osteomyelitis in Rats - Zhou, Zubin; Pan, Chenhao; Lu, Ye; Gao, Youshui; Liu, Wei; Yin, Peipei; Yu, Xiaowei (Frontiers in Cellular and Infection Microbiology, 2017)
Osteomyelitis is commonly caused by Staphylococcus aureus. Both erythromycin and curcumin can suppress Staphylococcus aureus growth, but their roles in osteomyelitis are barely studied. We aim to explore the activities of erythromycin and curcumin against chronical osteomyelitis induced by methicillin-resistant Staphylococcus aureus (MRSA). Chronicle implant-induced osteomyelitis was established by MRSA infection in male Wistar rats. Four weeks after bacterial inoculation, rats received no treatment, erythromycin monotherapy, curcumin monotherapy, or erythromycin plus curcumin twice daily for two weeks. Bacterial levels, bone infection status, inflammatory signals and side effects were evaluated. Rats tolerated all treatments well, with no death or side effects such as diarrhea and weight loss. Two days after treatment completion, erythromycin monotherapy did not suppress bacterial growth and had no effect in bone infection, although it reduced serum pro-inflammatory cytokines tumor necrosis factor (TNF)-α and interleukin (IL)-6. Curcumin monotherapy slightly suppressed bacterial growth, alleviated bone infection and reduced TNF-α and IL-6. Erythromycin and curcumin combined treatment markedly suppressed bacterial growth, substantially alleviated bone infection and reduced TNF-α and IL-6. Combination of erythromycin and curcumin lead a much stronger efficiency against MRSA induced osteomyelitis in rats than monotherapy. Our study suggests that erythromycin and curcumin could be a new combination for treating MRSA induced osteomyelitis.